PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR IPA - Ika Wahyuningsih (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
This research has descriptively aimed to determine the tendency of natural science result study using Group Investigation learning model and conventional learning model. Comparatively aims to determine differences in natural science result study on both the learning model. The data analysis technique using t-test but previously performed analysis prerequisite test including normality test distribution and homogeneity of variance test. The result of descriptive research showed that the tendency on natural science result study Group Investigation learning model included the very high category, and the use of conventional learning model included the high category. The analysis shows that there are very significant differences in natural science result study on both the learning model. The average of natural science result study using Group Investigation learning model is higher than conventional learning model, so it can be concluded that the effect of Group Investigation learning model on natural science result study.